PENGARUH KUALITAS PELAYANAN, KINERJA PEGAWAI, DAN KOMPETENSI PEGAWAI TERHADAP KEPUASAN MASYARAKAT DI KELURAHAN PADEMANGAN TIMUR - Ela Romadhona (2022)
This study is a quantitative study that aims to determine whether there is an influence of service quality, employee performance, and employee competence on community satisfaction in the East Pademangan Village. This study used 100 respondents from the community population who used the services of the East Pademangan Village, the exact number of which was not known. The analytical technique used in this research is the path analysis method and data processing is carried out using SmartPLS 3.3.3. The results of the test show that (1) service quality has a significant effect on community satisfaction in East Pademangan Village. (2) employee performance has a significant effect on community satisfaction in East Pademangan Village. (3) employee competence has no significant effect on community satisfaction in the East Pademangan Village. (4) service quality, employee performance, and employee competence have a significant effect on community satisfaction in the East Pademangan Village.